2002
DOI: 10.1074/jbc.m111921200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-βII Is an Apoptotic Lamin Kinase in Polyomavirus-transformed, Etoposide-treated pyF111 Rat Fibroblasts

Abstract: The role of protein kinase C-␤ II (PKC-␤ II ) in etoposide (VP-16)-induced apoptosis was studied using polyomavirus-transformed pyF111 rat fibroblasts in which PKC-␤ II specific activity in the nuclear membrane (NM) doubled and the enzyme was cleaved into catalytic fragments. No PKC-␤ II complexes with lamin B1 and/or active caspases were immunoprecipitable from the NM of proliferating untreated cells, but large complexes of PKC-␤ II holoprotein and its catalytic fragments with lamin B1, active caspase-3 and -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 73 publications
4
33
0
Order By: Relevance
“…1C) (14). Different PKCs have also been shown to be involved in apoptogenesis as well as proliferation and other activities (25,27,30,31). Therefore, as expected, when CalC ÊE is driving oxidized lamin B1 destruction, it silences PKC-ß I and PKC-‰ and any indication of impending apoptogenesis ( Fig.…”
Section: The Drivers Of Calc êE Cytocidal Actionssupporting
confidence: 53%
“…1C) (14). Different PKCs have also been shown to be involved in apoptogenesis as well as proliferation and other activities (25,27,30,31). Therefore, as expected, when CalC ÊE is driving oxidized lamin B1 destruction, it silences PKC-ß I and PKC-‰ and any indication of impending apoptogenesis ( Fig.…”
Section: The Drivers Of Calc êE Cytocidal Actionssupporting
confidence: 53%
“…Of interest is that in mouse CMV, the BFRF1 homolog has been shown to recruit cellular PKC to dissolve the nuclear lamina, allowing virions to gain access to the nuclear membrane for primary envelopment (28). Since it has been shown that PKC-␤II is directly responsible for lamin B phosphorylation and solubilization (21) and that the selective PKC-␤ inhibitor hispidin reduces lamin B phosphorylation and totally prevents lamin B proteolysis (8), it might be of interest to investigate whether the use of selective PKC inhibitors might interfere with the correct intracellular localization of lamin B or with its interaction with BFRF1, ultimately leading to the lamina disassembly that is needed for the breakdown of the nuclear envelope.…”
Section: Discussionmentioning
confidence: 99%
“…During apoptosis, PKC␦, a novel PKC, has been shown to translocate to the nuclear membrane and to phosphorylate lamin B at the Cterminal domain, thereby inducing apoptotic lamina disassembly (4,6,9,10). PKC␤II has also been shown to phosphorylate and thereby solubilize lamin B (8). Conversely, PKC␣ has been shown to bind lamin A protein yet functions as an apoptosis inhibitor (9,20).…”
mentioning
confidence: 99%